Hysteretic Behavior of Beam-to-Column Joints with Cast Steel Connectors - Guofeng Xue; Wei Bao; Jin Jiang; Yongsong Shao (Shock and Vibration)
This study proposed a beam-to-column joint equipped with a new type of cast steel connector. The cast steel connector concentrated the primary portion of the deformation and energy dissipation of the joint and was installed with full bolted connections, rendering it a replaceable energy dissipation component and facilitating the rapid repair of the joint after an earthquake. Three full-scale specimens were fabricated and tested to investigate the hysteretic behaviors of the proposed joints under cyclic loadings. The results showed that the proposed cast steel connector exhibited reliable ductility and energy dissipation capacity. The beam-to-column joints with cast steel connectors under appropriate configuration can limit the deformation to the cast steel connector and protect the remaining joint components from plastic deformation. A more detailed finite element analysis was performed to investigate the hysteretic behavior of the joint further. The FEM results illustrated that the thickness of the vertical leg of the cast steel connector can significantly influence the stiffness and bearing capacity of the joint. Meantime, it would improve the hysteretic behavior effectively. The proposed beam-to-column joints with cast steel connectors can achieve the requirement of stiffness and load-bearing capacity and can be widely applicable in practical engineering.